Efektivitas Hidroterapi Terhadap Kemampuan Fungsional Anak Dengan Cerebral Palsy Flaccid. - Novitasari, Anggelia Putri; Pristianto, Arif; Waspada, Edy (Prosiding University Research Colloquium, 2023)
Background: Cerebral palsy is a non-progressive disorder that occurs due to damage to the immature brain and can cause neurological disorders, both motor and sensory system disorders. Objective: to determine the effectiveness of hydrotherapy in improving the ability of children with flaccid cerebral palsy. Results: After 4x therapy for gmfm the results have increased from T0-T1, for muscle strength after doing it for 4x from t0-t4 it has increased and the ability to balance standing and walking has increased. Conclusion: Hydrotherapy can improve the ability to balance standing and walking and can improve functional abilities in children with cerebral palsy.